2014
DOI: 10.1002/jat.3047
|View full text |Cite
|
Sign up to set email alerts
|

Renal cells exposed to cadmium in vitro and in vivo: normalizing gene expression data

Abstract: Cadmium (Cd) is a toxic metal with a long half-life in biological systems. This half-life is partly as a result of metallothioneins (MTs), metal-binding proteins with a high affinity for Cd. The high retention properties of the kidneys reside in proximal tubular cells that possess transport mechanisms for Cd-MT uptake, ultimately leading to more Cd accumulation. Researchers have studied MT-metal interactions using various techniques including quantitative real-time PCR (qPCR), an efficient tool for quantifying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…An additional problem is encountered when normalizing gene expression in experimentally manipulated tissues; in the context of this study, animals that had been exposed to a variety of chemicals, often at toxicological dose levels. Experimental manipulations can adversely affect gene expression levels in various tissues, including genes normally regarded as ‘stable housekeeping genes’ ( Das, Banerjee & Shapiro, 2013 ; DuBois et al, 2013 ; Martínez-Beamonte et al, 2011 ; Nair et al, 2014 ; Pohjanvirta et al, 2006 ; Santin et al, 2013 ; Silver et al, 2008 ; Taki, Abdel-Rahman & Zhang, 2014 ). Here, we have also shown that the expression of endogenous reference genes such as Tbp , B2m and Gapdh are affected in tissues having been exposed to chemicals during development.…”
Section: Discussionmentioning
confidence: 99%
“…An additional problem is encountered when normalizing gene expression in experimentally manipulated tissues; in the context of this study, animals that had been exposed to a variety of chemicals, often at toxicological dose levels. Experimental manipulations can adversely affect gene expression levels in various tissues, including genes normally regarded as ‘stable housekeeping genes’ ( Das, Banerjee & Shapiro, 2013 ; DuBois et al, 2013 ; Martínez-Beamonte et al, 2011 ; Nair et al, 2014 ; Pohjanvirta et al, 2006 ; Santin et al, 2013 ; Silver et al, 2008 ; Taki, Abdel-Rahman & Zhang, 2014 ). Here, we have also shown that the expression of endogenous reference genes such as Tbp , B2m and Gapdh are affected in tissues having been exposed to chemicals during development.…”
Section: Discussionmentioning
confidence: 99%
“…An additional problem is encountered when normalizing gene expression in experimentally manipulated tissues; in the context of this study, animals that had been exposed to a variety of chemicals, often at toxicological dose levels. Experimental manipulations can adversely affect gene expression levels in various tissues, including genes normally regarded as 'stable housekeeping genes' (Das et al 2013;DuBois et al 2013;Martínez-Beamonte et al 2011;Nair et al 2014;Pohjanvirta et al 2006;Santin et al 2013;Silver et al 2008;Taki et al 2014). Here, we have also shown that the expression of endogenous reference genes such as Tbp, B2m and Gapdh are affected in tissues having been exposed to chemicals during development.…”
Section: Discussionmentioning
confidence: 66%
“…The tubular damage is seen as a result of exposure to Cd at low dose for a long period or at high dose for a short period. "s a result, glomerular iltration speed is decreased and inally renal impairment is seen [31]. International "gency on Cancer Research I"RC classiies Cd as human carcinogenic Group 1 [3 ]; while European Union Food Safety "uthority EFS" also underlined this fact stating, and exposure of Cd would lead increased risk for lung, endometrium, urinary bladder, and breast cancer [33].…”
Section: Cadmium CDmentioning
confidence: 99%